Migraines and keloids: a 15-year Taiwan claim database analysis. Issue 1160 (4th February 2021) - Lu, Ying-Yi; Qin, Hao; Lu, Chun-Ching; Wu, Ming-Kung; Zhang, Cong-Liang; Wu, Chieh-Hsin
Abstract: Background: Fibroproliferative lesions with intractable pruritus, pain and hyperesthesia that cause uncontrolled scar growth are known as keloids. Migraines are common upsetting headache disorders characterised by frequent recurrence and attacks aggravated by physical activity. Both keloids and migraines can cause physical exhaustion and discomfort in patients; they have similar pathophysiological pathways, that is, the transforming growth factor-β1 gene and neurogenic inflammation. Objective: To investigate subsequent development of migraines in patients with keloids. Methods: Data were retrieved from the Taiwan National Health Insurance Research Database. The keloids group included patients aged 20 years and older with a recent diagnosis of keloids(n=9864). The non-keloids group included patients without keloids matched for gender and age at 1–4 ratio (n=39 456). Migraine risk between groups was measured by Cox proportional hazards regression models. Incidence rates and hazard ratios were calculated. Results: During the study period, 103 keloids patients and 323 non-keloids patients developed migraines. The keloids patients had a 2.29-fold greater risk of developing migraines compared with the non-keloids group after adjustment for covariates (1.81 vs 0.55 per 1000 person-years, respectively). In the keloids group, female or patients younger than 50 years were prone to developing migraines. Conclusion: The higher tendency to develop migraines in the keloids group in comparison with the non-keloids group suggests that keloids could be a predisposing risk factor for migraine development in adults. Keloids patients who complain of headaches should be examined for migraines.